2023
DOI: 10.1039/d2sm00683a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling rheology via boundary conditions in dense granular flows

Abstract: Boundary shape, particularly roughness, strongly controls the amount of wall slip in dense granular flows. In this paper, we aim to quantify and understand which aspects of a dense granular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Wall shear stress not only induces the movement of the material but also directly influences the velocity gradient and slip velocity. This is observed in the work of Kalyon, 103 where it is shown that the applied shear stress determines the velocity profile in the fluid and the extension of wall slip.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Wall shear stress not only induces the movement of the material but also directly influences the velocity gradient and slip velocity. This is observed in the work of Kalyon, 103 where it is shown that the applied shear stress determines the velocity profile in the fluid and the extension of wall slip.…”
Section: Resultsmentioning
confidence: 61%
“…The intrinsic properties of the material, such as its viscosity and yield stress, along with the non-uniform distribution of the applied stress and the characteristics of the internal gel network, contribute to the persistence of slip. 102,103 Nevertheless, it is possible to determine that there is a value within a range of low shear stresses where elastic (solid-like) and viscous behaviors coexist, 104 from which wall slip occurs and the material can start yielding from a rest state. In other words, there is a transition state markedly affected by wall slip that facilitates the onset of flow with low shear stresses and significant deformations.…”
Section: Rheological Creep Testmentioning
confidence: 99%
“…Such wall effects are common in cohesionless packings and their presence together with a small gradient of forces from the walls towards the center of the box indicate that mesoscopic force inhomogeneities occur in our system on top of the well-known particle scale force inhomogeneity. 60,69–73 At higher cohesion (Fig. 13(b)), we observe both compressive and tensile force chains.…”
Section: Bonding Structurementioning
confidence: 87%
“…This interpretation is consistent with observations of aging in jammed and confined amorphous solids (C. Cao et al., 2017; J. Liu et al., 2020). Rough boundaries in slowly sheared granular materials not only frustrate ordering of grains near the boundary, but are also responsible for large‐magnitude force‐chain fluctuations (Fazelpour & Daniels, 2021, 2023; Fazelpour et al., 2022); this could be the “soft‐spot injection” mechanism. To sustain creep indefinitely, as appears to occur in nature on hillslopes, soil creep must be rejuvenated by the continuous injection of energy or disorder.…”
Section: Discussionmentioning
confidence: 99%